Devotion : an epic story of heroism and friendship ; adapted for young adults - Makos, Adam (Delacorte Press, 2022)
"A young adult adaptation of the national bestseller that details the true story of two Navy pilots from divergent racial and economic backgrounds who forge a deep friendship during the Korean War as they face extraordinary circumstances." --Amazon.com.